Study on the milk market in the period 2017-2021 - Diana Creţu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This article presents the milk market in the period 2017-2021 highlighting aspects regarding the evolution of the herd (cows), milk production, price, consumption, import, export, market characteristics, the main dairy producers in Romania, but also a series of conclusions that are the basis of this study. The research method used in the study is statistical data processing and economic analysis of data. Cow's milk is composed of 3.5 percent fat, 9 percent milk solids and 87.5 percent water. The main protein (80 percent) is casein. The milk of certain mammals, including cows, sheep, goats, buffaloes and yaks, is collected for human consumption, either directly, usually after pasteurization, or processed into dairy products such as cream, butter, yoghurt, ice cream or cheese. Milk is a complete food that contains all the nutrients that the human body needs. Cow's milk is the most appreciated by the consumer and the most accessible in terms of price, which are the main reasons why I chose to study this segment.
Keywords: Q11; Q13; L11; 330; cow milk; price; consumption; evolution